Lengger Lanang Dance Culture From the Perspective of Muslim-Friendly Tourism - Bagus Syarifuddin Latif; Rais A Yudian (Jurnal Toursci, 2026)
Background, The Lengger Lanang Dance is a traditional Banyumas art form that possesses cultural, historical, and spiritual values. Its uniqueness lies in the fact that the performers are male dancers who appear to resemble women. In the context of the growing development of Muslim-friendly tourism, the existence of Lengger Lanang has generated various perspectives regarding its compatibility with Islamic values. Aim, This study aims to analyze the Lengger Lanang Dance from the perspective of Muslim-friendly tourism. Methods, This research employed a qualitative descriptive approach. Data were collected through interviews, observations, and documentation. Results, The findings reveal that the Lengger Lanang Dance is a cultural heritage that embodies historical, social, philosophical, and religious values. Islamic values are reflected in the sindhenan songs, dance movements, and symbolic meanings of the performance, which convey messages of piety, morality, patience, and harmonious relationships between humans, God, and fellow human beings. Although certain aspects, particularly the appearance of male dancers resembling women, may be considered sensitive within the framework of Muslim-friendly tourism, the dance should not be evaluated solely based on its visual representation. Instead, it should be understood contextually through its cultural significance and moral teachings. Conclusions and From the perspective of Muslim-friendly tourism, the Lengger Lanang Dance cannot be assessed merely by the appearance of male dancers who resemble women. A more comprehensive understanding is required, taking into account the cultural values, philosophical meanings, and moral messages embedded in the performance.